A genome wide association study of plasma uric acid levels in obese cases and never‐overweight controls. (24th May 2013) - Li, Wei‐Dong; Jiao, Hongxiao; Wang, Kai; Zhang, Clarence K.; Glessner, Joseph T.; Grant, Struan F.A.; Zhao, Hongyu; Hakonarson, Hakon; Arlen Price, R.
Abstract : Objective: To identify plasma uric acid‐related genes in extremely obese and normal weight individuals using genome‐wide association studies (GWASs). Design and Methods: Using genotypes from a GWAS focusing on obesity and thinness, quantitative trait association analyses (PLINK) for plasma uric acid levels in 1, 060 extremely obese individuals (BMI > 35 kg/m 2 ) and normal‐weight controls (BMI < 25kg/m 2 ) were performed. In 961 samples with uric acid data, 924 were females. Results: Significant associations were found in SLC2A9 gene SNPs and plasma uric acid levels (rs6449213, P = 3.15 × 10 –12 ). DIP2C gene SNP rs877282 also reached genome‐wide significance ( P = 4.56 × 10 –8 ). Weaker associations ( P < 1× 10 –5 ) were found in F5, PXDNL, FRAS1, LCORL, and MICAL2 genes. Besides SLC2A9, three previously identified uric acid‐related genes ABCG2 (rs2622605, P = 0.0026), SLC17A1 (rs3799344, P = 0.0017), and RREB1 (rs1615495, P = 0.00055) received marginal support in our study. Conclusions: Two genes/chromosome regions reached genome‐wide association significance ( P < 1 × 10 –7, 550K SNPs) in our GWAS: SLC2A9, the chromosome 2 60.1 Mb region (rs6723995), and the DIP2C gene region. Five other genes ( F5, PXDNL, FRAS1, LCORL, and MICAL2 ) yielded P < 1 × 10 –5 . Four previous reported associations were replicated in our study, including SLC2A9, ABCG2, RREB, and SLC17A1 .